THE LEGAL PROBLEMS OF TRADITIONAL CULTURAL EXPRESSIONS AS INTELLECTUAL PROPERTY WITH COMMUNAL OWNERSHIP - Muryanto, Yudho Taruno; Kharisma, Dona Budi; Assidiqi, Imam Dzaki Hidayad (UNISSULA, 2024)
This legal research aims to analyze arrangements regarding communal legal protection of traditional cultural expressions based on Government Regulation Number 56 of 2022 concerning Communal Intellectual Property, and it also seeks to identify legal problems in the practice of protecting Communal Intellectual Property in Indonesia where various cases of unilateral claims against the inheritance of Traditional Cultural Expressions by other countries, such as Malaysia's claim for Pendet Dance, Wayang Art, and Reog; Germany’s claim for Distinctive Ornamental Frame from Jepara; and China’s claim for Batik Pesisir’s motif. There find legal problems. First, the intellectual property legal protection regime in Indonesia is still individualistic. Second, Insufficient communal intellectual property legal instruments. Last, a low legal culture in Indonesian society. Based on these findings, that the government need to amendment the protection of Traditional Cultural Expressions of Communal Intellectual Property through substance reform in Act No. 28 of 2014 about Copyright and develop one database of Communal Intelectual Property.